The wicked king ebook - Black, Holly (Folk of the Air, 2019)
The enchanting and bloodthirsty sequel to the New York Times bestselling novel The Cruel Prince. You must be strong enough to strike and strike and strike again without tiring. The first lesson is to make yourself strong. After the jaw-dropping revelation that Oak is the heir to Faerie, Jude must keep her brother safe. To do so, she has bound the wicked king, Cardan, to her, and made herself the power behind the throne. Navigating the constantly shifting political alliances of Faerie would be difficult enough if Cardan were easy to control. But he does everything in his power to humiliate and undermine her even as his fascination with her remains undiminished. When it becomes all too clear that someone close to Jude means to betray her, threatening her own life and the lives of everyone she loves, Jude must uncover the traitor and fight her own complicated feelings for Cardan to maintain control as a mortal in a Faerie world.